2009
DOI: 10.1016/j.cell.2009.09.014
|View full text |Cite
|
Sign up to set email alerts
|

The Argonaute CSR-1 and Its 22G-RNA Cofactors Are Required for Holocentric Chromosome Segregation

Abstract: SUMMARY RNAi-related pathways regulate diverse processes, from developmental timing to transposon silencing. Here, we show that in C. elegans the Argonaute CSR-1, the RNA-dependent RNA polymerase EGO-1, the Dicer-related helicase DRH-3, and the Tudor-domain protein EKL-1 localize to chromosomes and are required for proper chromosome segregation. In the absence of these factors chromosomes fail to align at the metaphase plate and kinetochores do not orient to opposing spindle poles. Surprisingly, the CSR-1 inte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

48
894
2

Year Published

2010
2010
2022
2022

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 437 publications
(963 citation statements)
references
References 56 publications
(70 reference statements)
48
894
2
Order By: Relevance
“…Consistent with P granules functioning as regulators of mRNA accumulation in the germline, many RNAi factors localize to P granules, including Dicer/DCR-1, the RNAdependent RNA polymerase EGO-1, and the argonaute proteins PRG-1 and CSR-1 (Batista et al 2008;Claycomb et al 2009). PRG-1 is a Piwi-related argonaute that prevents the expression of foreign genetic elements, including transposon and transgene mRNAs.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Consistent with P granules functioning as regulators of mRNA accumulation in the germline, many RNAi factors localize to P granules, including Dicer/DCR-1, the RNAdependent RNA polymerase EGO-1, and the argonaute proteins PRG-1 and CSR-1 (Batista et al 2008;Claycomb et al 2009). PRG-1 is a Piwi-related argonaute that prevents the expression of foreign genetic elements, including transposon and transgene mRNAs.…”
Section: Discussionmentioning
confidence: 99%
“…This information could then be relayed back into the nucleus to repress inappropriately activated, soma-specific genes through epigenetic mechanisms (Kasper et al 2014; Figure 8). CSR-1, another P granule-associated argonaute, recognizes its targets through associated 22G-RNAs that base pair with germline-expressed mRNAs including those important for embryogenesis (Claycomb et al 2009). Interestingly, CSR-1 was recently found to tune the levels of certain germline mRNAs in a manner that is dependent on its slicer activity (Gerson-Gurwitz et al 2016).…”
Section: Discussionmentioning
confidence: 99%
“…S6). Recent studies have shown that DRH-3 is required for germline development and RNAi by participating in the biogenesis of 22G RNAs (25,38,39), suggesting a possible role for DRH-3 in antiviral RNAi. We investigated FHV replication and Orsay virus infection in worms containing the ne4253 allele of drh-3.…”
Section: The Helicase and Ctd Domains Of Rig-i Were Functional In A Fmentioning
confidence: 99%
“…Some reports have suggested that it is as a component of germline perinuclear P--granule structures which are sites of mRNA export and possibly degradation (KAWASAKI et al 1998;SHETH et al 2010), and others have shown that these P--granules' structure or stability depends, at least indirectly, on RNAi components including CSR--1, EGO--1, DCR--1, DRH--3, PRG--1, and RDE--4 (BESHORE et al 2011;CLAYCOMB et al 2009;SPIKE et al 2008; UPDIKE and STROME 2009). While PGL--1's link to RNAs is genetically and biochemically well--established (HANAZAWA et al 2011;SCHISA et al 2001), especially for those in the germline, there are conflicting reports on its role in RNAi.…”
Section: Pgl--1's Link To Rnaimentioning
confidence: 99%